Delivery mode and maternal and neonatal outcomes of combined spinal–epidural analgesia compared with no analgesia in spontaneous labor: A single‐center observational study in Japan. Issue 3 (20th January 2020) - Kurakazu, Masamitsu; Umehara, Nagayoshi; Nagata, Chie; Yamashita, Yoko; Sato, Masaki; Sago, Haruhiko
Abstract: Aim: We aimed to assess the outcomes of combined spinal–epidural (CSE) analgesia compared with no analgesia in spontaneous labor. Methods: We performed a retrospective cohort study of deliveries between 2008 and 2014 comparing two groups based on the use of CSE analgesia in both nulliparous and multiparous women. Adjusted odds ratios (aOR) were calculated using logistic regression analysis. Results: Among 5247 (3334 nulliparous, 1913 multiparous) singleton deliveries, 3041 (2045, 996, respectively) patients received CSE analgesia and 2206 (1289, 917, respectively) had no analgesia. CSE analgesia was associated with increased risk of oxytocin augmentation ( P  < 0.01), prolonged duration of labor ( P  < 0.01), instrumental delivery (aOR, 3.35; 95% confidence interval (CI), 2.69–4.19 for nulliparous and aOR, 2.13; 95% CI, 1.32–3.53 for multiparous women), blood loss volume during vaginal delivery ( P  < 0.01), meconium‐stained amniotic fluid (aOR, 1.23; 95% CI, 1.02–1.51 and aOR, 1.39; 95% CI, 1.01–1.93) and Apgar score less than 7 at 1 min (aOR, 1.85; 95% CI, 1.28–2.74 and aOR, 2.65; 95% CI, 1.35–5.61) in both nulliparous and multiparous women, respectively, and umbilical arterial blood gas pH less than 7.15 (aOR, 2.69; 95% CI, 1.35–5.75) and umbilical arterial blood gas pH less than 7.10 (aOR, 3.69; 95% CI, 1.11–16.69) in multiparous women. There was no significant difference in incidence of cesarean delivery or Apgar score less than 7 at 5 min. Conclusion: We observed several increased risks in obstetric and neonatal outcomes among pregnant women who received CSE analgesia during labor. Preparations for these risks are needed when administering CSE analgesia during labor.